Peranan Ilmu Al-Qur'an dalam Penafsiran Ayat-Ayat Mutasyabihat - Ariella Zaneta; Muhamad Rifa’i Subhi (ejournal.nurulqadim.ac.id, 2024)
This study is behind the interpretation of the Quran's mutasaybih verse is a key aspect of Islamic hermeneutics. Biblical mutasya verses are verses that have diverse potential meanings and require a careful scientific approach to expressing a comprehensive message of knowledge about the Quran playing an important role in that they facilitate a proper understanding of these verses. The formula for the problem is: (1) How does the science of the Quran play an important role in revealing the meaning of the Quran's mutany? (2) What factors contribute to misinterpretation? (3) Why is understanding the Qur'an necessary to interpret complex Qur'an verses such as the Quran's mutuality? (4) How can practical applications of the Quran help clarify the meaning of the Qur'an verses? (5) How do various ways of understanding complex scriptures affect the overall understanding of the Quran? The research methods used in this study are descriptive, analytical methods by analyzing related scientific literature, including classical and contemporary interpretations of the Qur'an that apply Qur'an science. The data is obtained through library studies to explore scientific approaches to interpretation of the mutational scriptures. The results of this study show that the science of the Qur'an plays a vital role in the interpretation of the mutational scriptures by providing a clear and comprehensive methodological framework. The principles of ushul al-tafsir and the science of al-balaghah are used to interpret verses that have double potential meanings. The Arabic understanding, historical context, and rhetoric of the Qur'an are key in accurately deciphering the meaning of the Qur'an verses. The solution used in overcoming the mutasihat verses is important for mufassir to adopt a multidisciplinary approach to Qur'an science. These include mastery of Arabic, knowledge of historical context, proper application of interpretation principles, and understanding of the rhetoric of the Qur'an. Thus, Qur'an science can provide a profound and applicative insight into Qur'an messages relevant to Muslims in everyday life.